#1**+2 **

\(\text{The cheat way is to remember the vertex of $a x^2 + bx + c$ occurs at $x=-\dfrac{b}{2a}$}\\~\\ \text{we see here that $x=-\dfrac{-2}{2}=1,~f(1) = 1-2-35=-36$}\\ v=(1,-36)\\~\\ \text{A better way (imo) is to complete the square}\\~\\ x^2-2x-35 = x^2 - 2x + 1-1-35 = (x-1)^2 - 36\\~\\ \text{and we can read the vertex right off as $(1,-36)$}\)

.Rom May 23, 2019

#1**+2 **

Best Answer

\(\text{The cheat way is to remember the vertex of $a x^2 + bx + c$ occurs at $x=-\dfrac{b}{2a}$}\\~\\ \text{we see here that $x=-\dfrac{-2}{2}=1,~f(1) = 1-2-35=-36$}\\ v=(1,-36)\\~\\ \text{A better way (imo) is to complete the square}\\~\\ x^2-2x-35 = x^2 - 2x + 1-1-35 = (x-1)^2 - 36\\~\\ \text{and we can read the vertex right off as $(1,-36)$}\)

Rom May 23, 2019